2008
DOI: 10.1002/elps.200800054
|View full text |Cite
|
Sign up to set email alerts
|

Impurity analysis of pharmaceuticals using capillary electromigration methods

Abstract: This review deals with the determination of impurities in pharmaceuticals by electromigration methods in the capillary format. These separation methods are either based on the different effective mobility of the charged analytes (as in zone electrophoresis and isotachophoresis) or include hybrid methods such as micellar electrokinetic chromatography, microemulsion electrokinetic chromatography and electrochromatography. The pharmaceutically active compounds under consideration belong to chemotherapeutic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 149 publications
(96 reference statements)
0
22
0
Order By: Relevance
“…Finally, it was concluded that the method is suitable for routine quality control and stability analyses, especially in the developing world (Jindal et al 1994). Jouyban and Kenndler (2008) reviewed the applicability of capillary electrophoresis (CE) methods for the analysis of pharmaceutical impurities. In addition, they discussed the applications of these methods in various groups of compounds such as chemotherapeutic agents, central nervous system (CNS) drugs, histamine receptor and cardiovascular drugs.…”
Section: Tlc/hptlc Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was concluded that the method is suitable for routine quality control and stability analyses, especially in the developing world (Jindal et al 1994). Jouyban and Kenndler (2008) reviewed the applicability of capillary electrophoresis (CE) methods for the analysis of pharmaceutical impurities. In addition, they discussed the applications of these methods in various groups of compounds such as chemotherapeutic agents, central nervous system (CNS) drugs, histamine receptor and cardiovascular drugs.…”
Section: Tlc/hptlc Methodsmentioning
confidence: 99%
“…Mahuzier et al (2001) demonstrated the poor sensitivity of CE based methods, in comparison to other separation methods. The problem of limited sensitivity of CE methods can be solved either by the use of detection methods with sensitivity higher than UV absorption or by pre-concentration of the analytes (Jouyban and Kenndler, 2008).…”
Section: Tlc/hptlc Methodsmentioning
confidence: 99%
“…Further examples can be found in several reviews, for example [5][6][7]79]. The application of CE in drug impurity analysis has been summarized [79,80]. Table 1 clearly reflects the general trend that CDs are by far the most widely used chiral selectors although some studies utilized other additives such as BSA [81], maltodextrin [82], (+)-18C6H4 [83], ligand exchange [84] or the chiral ionic liquid ethylcholine bis(trifluoromethylsulfonyl) Baclofen α-CD (18 mM) 0.1 M sodium borate, pH 9.9, 1% acetonitrile 2-10 μg/ml, analysis of racemic bulk drug and tablets [103] Benzimidazole derivatives Chloroquine SBE-β-CD (30 mg/ml) 100 mM sodium phosphate, pH 2.5 0.02%, analysis of laboratory sample [108] Clopidogrel Sulfated β-CD (5%) 10 mM triethylamine/phosphoric acid 0.08-0.33 μg/ml, minor enantiomer and related substances [109] Dexamphetamine HDAS-β-CD (10 mg/ml) 0.1 M sodium phosphate buffer, pH 2.5 0.06%, minor enantiomer and charged related substances [91] Dexamphetamine Sulfated β-CD (25 mg/ml), SBE-β-CD (80 mg/ml) 50 mM sodium phosphate buffer, pH 2.5 0.01-0.02%, minor enantiomer and related substances [92] Dexamphetamine Sulfated β-CD (5.5%) 1.5% SDS, 0.5% ethyl acetate, 3.5% 1-butanol, 2.5% 2-propanol and 92% 50 mM sodium phosphate buffer, pH 3.0 0.05-0.2%, minor enantiomer and related substances [93] Econazole HP-γ-CD (40 mM) 50 mM SDS in 20 mM phosphate buffer, pH 8.0…”
Section: Pharmaceutical Analysismentioning
confidence: 99%
“…While HPLC remains the most common technique for the analysis of benzodiazepines, 7,9,14,15 mainly in reversed phase (RP) mode, several capillary zone electrophoresis (CZE) methods have recently been developed. 2,16,17 CZE represents an interesting alternative to HPLC for determination of pharmaceuticals, in general, 18,19 mainly because of its higher efficiency in comparison with HPLC. 20 The aim of this work was to develop and optimize separation conditions for a set of seven 1,4-BZDs in RP-HPLC and CZE with UV detection and compare these methods in terms of efficiency, analysis time, resolution, elution order and basic validation parameters.…”
Section: Introductionmentioning
confidence: 99%